Popper, o historicismo, e o método das ciências sociais - Costa, Paulo Alberto Viana da (2011)
From the critic of the historicism and holism it searches to present the method of the social sciences as it is proposed by Karl Popper. After a short exposition about the method of the natural sciences and some of its components, namely the concepts of deductive method, falseability, and corroboration, historicism is defined and criticized. Through the use of some examples based in XX century physics it shows how is possible to disprove historicism, showing that a prima facie deterministic theory can not ensure the determism of the world, nor of its forecasts. It defines the so called situational analysis, which maintains social that the social sciences task is the explanation of typical situations. Indicates the origin of this concept e its major influences as well as its limits. Exhibits why situational analysis can not be the sole method of the social sciences, and why psychology can not be eliminated from the study of some social situations.